A Systematic Review on Fuzzy Linear & Non-Linear Model and Its Problems in Real World: Advancements in Fuzzy Regression Models and their Applications (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Fuzzy regression model has been generally utilized as a part of late years all through the globe. In perspective of this, an endeavor has been made in this exploration paper to introduce the audit of fuzzy regression model for better estimation and expectation. The regression investigation is measurable apparatus utilized for expectation. As we realize that the regression examination takes after Gaussian assumptions, some of the time dataset is too little and ambiguous. In this circumstance fuzzy regression gives better outcomes when contrasted with conventional apparatuses. The present survey is giving the data writing and late techniques created by various Author. Additionally this survey feature on the work done by various creators in various field of linear programming issue on fuzzy slightest square and fuzzy interval estimation. The fuzzy regression models were giving preferable accuracy over conventional regression model. In perspective of this an endeavor has been made in this paper to survey late work done in the field of fuzzy regression. The survey has demonstrated that larger part of concentrates on fuzzy regression models with linear programming approach utilizing diverse fuzzy numbers.